Safety and effectiveness of non‐insulin glucose‐lowering agents in the treatment of people with type 2 diabetes who observe Ramadan: a systematic review and meta‐analysis. Issue 7 (12th April 2015) - Gray, L. J.; Dales, J.; Brady, E. M.; Khunti, K.; Hanif, W.; Davies, M. J.
<x xml:space="preserve">Abstract</x> Aim To determine which non‐insulin glucose‐lowering treatment regimens are most appropriate in people with type 2 diabetes who choose to fast during Ramadan. Methods Electronic databases were searched for randomized controlled trials (RCTs) and observational studies that compared non‐insulin glucose‐lowering agents in people with type 2 diabetes fasting during Ramadan. Those studies which reported hypoglycaemia, weight and glycated haemoglobin (HbA1c) change were included. Data were pooled using random effects models. Results A total of 16 studies were included: 9 RCTs and 7 observational studies. There was evidence that dipeptidyl peptidase‐4 (DPP‐4) inhibitors led to fewer hypoglycaemic events compared with sulphonylureas. Sitagliptin significantly reduced the number of patients with ≥1 hypoglycaemic episodes during Ramadan [risk ratio (RR) 0.48, 95% confidence interval (CI) 0.36, 0.64; p > 0.0001]. This was not replicated in the RCTs of vildagliptin, but a significant reduction was found in the observational studies (RR 0.28, 95% CI 0.10, 0.75; p = 0.01) with high heterogeneity (I2 = 86.7%). Significant reductions in HbA1c and weight were seen in the observational studies of vildagliptin versus sulphonylureas. The use of liraglutide led to significant weight loss (−1.81 kg, 95% CI −2.91, −0.71; p = 0.001) compared with sulphonylureas. Pioglitazone significantly increased weight compared with placebo (3.48 kg, 95% CI 2.82, 4.14; p < 0.0001). Conclusions The analysis supports the use of DPP‐4 inhibitors during Ramadan rather than sulphonylureas for reduction in hypoglycaemia without a cost to diabetes control and weight. The glucagon‐like peptide (GLP)‐1 agonist liraglutide provides clinical benefits, but more studies are required. RCTs of DPP‐4 inhibitors compared with GLP‐1 agonists and novel therapies including the sodium‐glucose co‐transporter 2 and α‐glucosidase inhibitors are needed to inform evidence‐based guidelines.